2023
DOI: 10.3389/fpsyg.2022.1017384
|View full text |Cite
|
Sign up to set email alerts
|

“Feeling It”: Links between elements of compassion and sexual well-being

Abstract: IntroductionCompassion may be a particularly important component of a sexual relationship as it facilitates needed self-awareness, understanding, and connection to frame deeply intimate expressions of sexual emotion and vulnerability. Given the lack of research on how broad concepts of compassionate elements may be linked to sexual well-being, we examine how mindfulness (an ability to maintain awareness in the present moment), compassionate relational attitudes (i.e., accessibility, responsiveness, and engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…The positive association between the CLS-P-SF score and satisfaction with sex life is consistent with previous research (Neto, 2012b;Neto & Wilks, 2017). This finding is also consonant with work indicating that females' and males' compassionate attitudes and behaviors had significant effects on their partner's sexual well-being (Fraser et al, 2023). These positive associations between CLS-P-SF scores, and sexual desire and satisfaction with sex life supported our fourth hypothesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The positive association between the CLS-P-SF score and satisfaction with sex life is consistent with previous research (Neto, 2012b;Neto & Wilks, 2017). This finding is also consonant with work indicating that females' and males' compassionate attitudes and behaviors had significant effects on their partner's sexual well-being (Fraser et al, 2023). These positive associations between CLS-P-SF scores, and sexual desire and satisfaction with sex life supported our fourth hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…Satisfaction with sex life represents a relevant correlate of well-being (Hatfield et al, 2020; Mark et al, 2014). Fraser et al (2023) examined the links between relational compassion and comprehensive measures of sexual well-being. These scholars showed that relational compassion may be a key facilitator of sexual well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, studies considering the role of compassion in relationships are limited (and recent), generally finding compassion to be associated with relationship outcomes like marital quality (McDonald et al, 2020). In terms of sexuality, results from prior research have suggested links between higher compassionate relational attitudes and increased sexual satisfaction and orgasm consistency (Fraser et al, 2023). However, Fraser et al (2023) conceptualized and measured compassion as attitudes and behaviors (separately), like forgiveness.…”
Section: Compassionmentioning
confidence: 99%
“…In terms of sexuality, results from prior research have suggested links between higher compassionate relational attitudes and increased sexual satisfaction and orgasm consistency (Fraser et al, 2023). However, Fraser et al (2023) conceptualized and measured compassion as attitudes and behaviors (separately), like forgiveness. Although these are strong proxies for compassionate attitudes and behaviors respectively, this conceptualization of compassionate behaviors is distinct from compassion as a psychological trait.…”
Section: Compassionmentioning
confidence: 99%
“…A prerequisite to communicating effectively about inner feelings is that one is actually aware of them (Burgoon et al, 2000). In an intimate relationship, paying attention benefits relational and sexual outcomes (Leavitt, Maurer, et al, 2021; Fraser et al, 2022; Busby et al, 2022). These are just a few examples of how paying attention may play an important role in the quality of close relationships.…”
Section: Introductionmentioning
confidence: 99%